; Development of cooperatives in Uzbekistan and their recent transformation - Olim Murtazaev (Leibniz Institute of Agricultural Development in Transition Economies (IAMO), 2018)
– With the transition to a market economy, there have been fundamental changes in the agriculture of Uzbekistan. At the onset of agricultural reforms, state farms were transformed into public, then into cooperative farms, i.e. shirkats. Finally, after the latter were disagregated, special attention was paid to the development of individual and dehkan farms via introduction of private property. At the same time, inter-farm economic relations formed over a decade had a negative impact on the development of agriculture. Economic relations with processing industries and enterprises became obstacles to the development of agriculture. Processing industries, as well as farms- monopolies did not timely pay for the delivered raw materials, prolonged the timing of product acceptance, set high prices for delivered services, and procured raw inputs at low prices. As a result, this led to the loss of production, increased costs, decreased quality of raw materials, and of course, to deterioration of farm incomes. To respond to this, a number of decrees were adopted. These documents repeatedly noted the need for cooperation between newly-established individual farms, and also discussed its role and importance in the societal development. To realize the above tasks set for the agrarian and industrial sectors of Uzbekistan, it was necessary to unite small farms into larger agricultural cooperatives in production, processing, storage, transportation and marketing activities. The creation of specialized cooperatives will solve a number of socio-economic problems, i.e. first of all, ensure integration of producers and consumers, reduce transaction costs, and reduce marketing channels which lower farm gate prices. The activities that combine efforts of a group of agricultural producers will increase the efficiency of resource use.
urn:nbn:de:gbv:3:2-100776
Keywords: 330; land reform; shirkat farms; cooperatives; individual farms; dekhkans; agricultural cooperative